Studi Komparasi Model Pembelajaran Projek Based Learning (PjBL) dan Jigsaw Terhadap Hasil Belajar IPS SDN 2 Abepura - Chelsi Yuliana S (Jayapangus Press, 2023)
Learning outcomes are one level of measurement of learning objectives for students which are called Learning Outcomes. that way the delivery of learning material requires modification or appropriate learning design to achieve the objectives of teaching. The fact is that at SDN 2 Abepura there are still teachers who teach using conventional methods. This study aims to determine higher learning outcomes than the PjBL and Jigsaw learning models. The study used a quasi-experimental approach with a pretest-posttest non-equivalent control group design. calculated using the Gaint Score with 1) Social Studies learning outcomes for Hindu Buddhist kingdoms using the Project Based Learning (PjBL) learning model are higher with an average of 0.65 than using the Jigsaw learning model 0.42 2). Social studies learning outcomes with Hindu Buddhist kingdom material in the aspects of applying, analyzing, evaluating, creating with the Project Based Learning (PjBL) learning model are higher than the Jigsaw learning model. After following this research it can be concluded that the PjBL learning model has higher learning outcomes compared to the Jigsaw model.